Developmental Exposure to Bisphenol A Modulates Innate but Not Adaptive Immune Responses to Influenza A Virus Infection - Roy, Anirban; Bauer, Stephen M.; Lawrence, B. Paige (PLOS ONE, 2012)
Bisphenol A (BPA) is used in numerous products, such as plastic bottles and food containers, from which it frequently leaches out and is consumed by humans. There is a growing public concern that BPA exposure may pose a significant threat to human health. Moreover, due to the widespread and constant nature of BPA exposure, not only adults but fetuses and neonates are also exposed to BPA. There is mounting evidence that developmental exposures to chemicals from our environment, including BPA, contribute to diseases late in life; yet, studies of how early life exposures specifically alter the immune system are limited. Herein we report an examination of how maternal exposure to a low, environmentally relevant dose of BPA affects the immune response to infection with influenza A virus. We exposed female mice during pregnancy and through lactation to the oral reference dose for BPA listed by the US Environmental Protection Agency, and comprehensively examined immune parameters directly linked to disease outcomes in adult offspring following infection with influenza A virus. We found that developmental exposure to BPA did not compromise disease-specific adaptive immunity against virus infection, or reduce the host’s ability to clear the virus from the infected lung. However, maternal exposure to BPA transiently reduced the extent of infection-associated pulmonary inflammation and anti-viral gene expression in lung tissue. From these observations, we conclude that maternal exposure to BPA slightly modulates innate immunity in adult offspring, but does not impair the anti-viral adaptive immune response, which is critical for virus clearance and survival following influenza virus infection.